Hubble Tarantula Treasury Project: VI. identification of pre-main-sequence stars using machine-learning techniques - Ksoll, Victor F.; Gouliermis, Dimitrios A.; Klessen, Ralf S.; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. The Hubble Tarantula Treasury Project (HTTP) has provided an unprecedented photometric coverage of the entire starburst region of 30 Doradus down to
Gesehen am 01.02.2019